Review: Miglitol has potential as a therapeutic drug against obesity. Issue 1 (December 2015) - Sugimoto, Satoru; Nakajima, Hisakazu; Kosaka, Kitaro; Hosoi, Hajime
Abstract The number of obese patients has increased annually worldwide. Therefore, there is a strong need to develop a new effective and safe anti-obesity drug. Miglitol is an alpha-glucosidase inhibitor (αGI) that is commonly used as an anti-diabetic drug, and there is growing evidence that it also has anti-obesity effects. Miglitol has been shown to reduce body weight and ameliorate insulin resistance in both clinical trials with adult patients and in rodent models of obesity. Although the specific mechanism of action of this effect remains unclear, some mechanisms have been suggested through experimental results. Miglitol has been shown to inhibit adipogenesis of white adipocytesin vitro, activate brown adipose tissue (BAT) in mice, influence bile acid metabolism in mice, and regulate the secretion of incretin hormones in humans. Among these results, we consider that BAT activation is likely the definitive mediator of miglitol's anti-obesity effect. A unique advantage of miglitol is that it is already used as an anti-diabetic drug with no severe side effects, whereas many of the anti-obesity drugs developed to date have been withdrawn because of their severe side effects. Miglitol is currently used clinically in a limited number of countries. In this review, we provide an overview of the state of research on miglitol for obesity treatment, emphasizing that it warrants more detailed attention. Overall, we demonstrate that miglitol shows good potential as a therapeutic for the treatment of obesity. Thus, we believe that further investigations of how it exerts its anti-obesity effect will likely contribute to the development of a new class of safe and effective drugs against obesity.